High Dimensional Neurocomputing Growth, Appraisal and Applications - Tripathi, Bipin Kumar; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
The book presents a coherent understanding of computational intelligence from the perspective of what is known as "intelligent computing" with high-dimensional parameters. It critically discusses the central issue of high-dimensional neurocomputing, such as quantitative representation of signals, extending the dimensionality of neuron, supervised and unsupervised learning and design of higher order neurons. The strong point of the book is its clarity and ability of the underlying theory to unify our understanding of high-dimensional computing where conventional methods fail. The plenty of application oriented problems are presented for evaluating, monitoring and maintaining the stability of adaptive learning machine. Author has taken care to cover the breadth and depth of the subject, both in the qualitative as well as quantitative way. The book is intended to enlighten the scientific community, ranging from advanced undergraduates to engineers, scientists and seasoned researchers in computational intelligence.
Neuro-Computing with High Dimensional Parameters -- Neuro-Computing in Complex Domain -- Higher Order Computational Model of Novel Neurons -- Neuro-Computing in Space -- High Dimensional Mapping -- Machine Recognition for Biometric Application in Complex Domain.
Keywords: Engineering; Pattern recognition; Biometrics (Biology).; Neural networks (Computer science).; Computational intelligence; Engineering; Computational Intelligence; Pattern Recognition; Mathematical Models of Cognitive Processes and Neural Networks; Biometrics; Electronic books